The Effect of Mind Mapping Based Imindmap Application on The Creativity and Concept Understanding of Students - Taadi, Darpia; Raharjo, Tri Joko; Deliana, Sri Maryati (Universitas Negeri Semarang, 2019)
This study was conducted by considering several problems appear in the field of study, such as the low creativity of the learning of IPS subject at Muhammadiyah Integrated Elementary School Ponorogo, the unavailability of the appropriate learning methods to improve the creativity and understanding concepts of the students at the school, teachers at the school are more often apply the lecture method in the teaching and learning IPS. This study has the purpose of determining the effect of the application of the Mind mapping method based Imindmap application on the creativity and conceptual understanding of students. This study was conducted at Muhammadiyah Integrated Elementary School Ponorogo, grade VA, and VB. This study applied the experimental method with random cluster sampling. The variables used in this study are the creativity and the understanding concept of students. The data collection method used was a questionnaire to obtain data on student creativity and tests to obtain the results of the understanding concepts of students. The technical analysis of the data used was Manova and t-test. The results of the study through the t-test of student creativity in the experimental group were obtained (t = -7.795; p < 0.01) significantly. Therefore, it can be concluded that the method of mind mapping based Imindmap application affects the creativity of students. The results of the study through the t-test of students' conceptual understanding in the experimental group were obtained (t = -6.807; p < 0.01) significantly. Therefore, it can be concluded that the method of mind mapping based Imindmap application affects the understanding concepts of students. Manova test results obtained from the Tests of Between-Subjects Effects of student creativity was (F(3.46) = 34,104; p < 0.01), conceptual understanding was (F(3.46) = 5,727; p < 0.01). The effect of the Mind mapping method based Imindmap application in increasing creativity is 69% ( = 0.690), and the conceptual understanding is 27% ( = 0.272). This study can be a useful input for teachers and prospective teachers in improving oneself about teaching in the digital era that is increasingly developing to achieve more creative, innovative, and easy to understand material and science and technology insight learning goals.